2009
DOI: 10.1073/pnas.0902279106
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive picture of phloem loading strategies

Abstract: Mechanisms of phloem loading in the minor veins of leaves are known for only a few species. We propose that there are a limited number of loading strategies for the primary photoassimilates, sucrose and sugar alcohols. These strategies can be predicted based on thermodynamic and anatomical considerations and identified by autoradiography of veins following uptake of 14 C-labeled compounds, analysis of leaf solute composition and concentrations, and plasmodesmatal counting. Experiments on 45 dicotyledonous spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
331
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 347 publications
(352 citation statements)
references
References 31 publications
13
331
0
1
Order By: Relevance
“…While sugar concentrations observed in plants generally span a wide range, this analysis provides a rationale for the observation that plants that use active sugar loading (data shown in figure 1c) typically have a higher sugar concentration than plants that use passive loading [15]. Active loaders expend metabolic energy to increase the sugar concentration in the phloem [21]. The process is driven by membrane transporters and sugar polymerization and occurs against a sugar concentration gradient.…”
Section: Sugar Transport In Plantsmentioning
confidence: 99%
“…While sugar concentrations observed in plants generally span a wide range, this analysis provides a rationale for the observation that plants that use active sugar loading (data shown in figure 1c) typically have a higher sugar concentration than plants that use passive loading [15]. Active loaders expend metabolic energy to increase the sugar concentration in the phloem [21]. The process is driven by membrane transporters and sugar polymerization and occurs against a sugar concentration gradient.…”
Section: Sugar Transport In Plantsmentioning
confidence: 99%
“…1,2 In apoplastic phloem loading species, sucrose transporters (SUTs) import sucrose from the apoplast into the companion cells and/or sieve elements. [3][4][5] In dicot plants, genetic and biochemical evidence has shown that SUTs function to phloem load sucrose in leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Three phloem loading strategies have been identified for Suc, two of which are thermodynamically active and the third passive (Reidel et al, 2009;Rennie and Turgeon, 2009;Turgeon, 2010a). In the more common active mechanism, apoplastic loading, Suc enters the apoplast and is pumped into sieve element-companion cell complexes by membrane-bound transporters, using energy derived from the proton motive force (Sauer, 2007).…”
mentioning
confidence: 99%